B-1 Cells May Drive Macrophages Susceptibility to Trypanosoma cruzi Infection - da Rocha, Raphael Francisco Dutra Barbosa; LaRocque-de-Freitas, Isabel Ferreira; Arcanjo, Angelica Fernandes; Logullo, Jorgete; Nunes, Marise Pinheiro; Freire-de-Lima, Celio Geraldo; Decote-Ricardo, Debora (Frontiers in Microbiology, 2019)
B-1 cells can directly and indirectly influence the immune response. These cells are known to be excellent producers of natural antibodies and can secrete a variety of immunomodulatory molecules. They are also able to differentiate into B-1 cell-derived phagocytes (B-1CDP). B-1 cells can modulate macrophages to become less effective, and B-1CDP cells are more susceptible in infection models. In this work, we investigated the microbicidal ability of these cells in Trypanosoma cruzi infection in vitro. The results show that macrophages from BALB/c mice are more susceptible to infection than macrophages from XID mice. The resistance observed in macrophages from XID mice was abolished in the presence of B-1 cells, and this event seems to be associated with IL-10 production by B-1 cells, which may have contributed to the decrease of NO production. Additionally, B-1CDP cells were more permissive to intracellular T. cruzi infection than peritoneal macrophages. These findings strongly suggest that B-1 cells and B-1CDP cells have a potential role in the persistence of the parasite in host cells.